2019
DOI: 10.1002/jsfa.9552
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of cocktail tomato yield and consumer‐oriented quality traits by potassium fertilization is driven by the cultivar

Abstract: BACKGROUND The market for cocktail tomatoes is growing continuously, mainly because of their good taste. Titratable acids (TA), total soluble solids (TSS) and dry matter (DM) contents correlate positively with good taste. So far, the impact of different potassium (K) applications on yield and consumer‐oriented quality traits has not been comprehensively described for cultivars of smaller fruits. To fill this gap, we tested the effect of different K fertilization regimes on three cultivars of small‐sized or coc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 44 publications
2
5
0
Order By: Relevance
“…Genotype is an important determinant of the extent of variability in carotenoid content of ripe tomato fruits ( 12 ). The red color value (a*) of our cultivars was lower than that of the cocktail cultivars studied in Sonntag et al ( 55 ), while the color values of the red-fruited salad cultivars (“Bocati F 1 ”, “Cappricia F 1 ”, “Roterno F 1 ”) were comparable to the results of Sonntag et al ( 55 ). The red color of the tomato fruits is due to the synthesis of lycopene and degradation of chlorophyll ( 56 ), while an orange genotype accumulates high levels of β-carotene in addition to a low-lycopene content ( 57 ).…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…Genotype is an important determinant of the extent of variability in carotenoid content of ripe tomato fruits ( 12 ). The red color value (a*) of our cultivars was lower than that of the cocktail cultivars studied in Sonntag et al ( 55 ), while the color values of the red-fruited salad cultivars (“Bocati F 1 ”, “Cappricia F 1 ”, “Roterno F 1 ”) were comparable to the results of Sonntag et al ( 55 ). The red color of the tomato fruits is due to the synthesis of lycopene and degradation of chlorophyll ( 56 ), while an orange genotype accumulates high levels of β-carotene in addition to a low-lycopene content ( 57 ).…”
Section: Discussionsupporting
confidence: 69%
“…The red color of the tomato fruits is due to the synthesis of lycopene and degradation of chlorophyll ( 56 ), while an orange genotype accumulates high levels of β-carotene in addition to a low-lycopene content ( 57 ). Increasing a* value, lycopene and ß-carotene were observed during ripening of red-fruited cultivars ( 55 ). Based on heritability and genotype by environment interaction, lycopene, which accounts for more than 85% of total carotenoids in many red-fruited cultivars ( 58 ), was the most environmentally sensitive trait ( 50 ).…”
Section: Discussionmentioning
confidence: 99%
“…These findings may explain the influence of K supply levels on total yields and plant DWs. This result was in line with Yurtseven et al (2005) and Sonntag et al (2019), who reported that significant yield increases with increasing K application [50,51]. However, Nzanza (2006) found that none of the applied K treatments had any significant effect on marketable tomato yield [28].…”
Section: K Application Influenced Cherry Tomato Growth By Regulating supporting
confidence: 83%
“…The results shown in Table 1 and Figure 1 were somewhat expected, since (Figure 1) is due to the important role that this nutrient plays in the translocation of photoassimilates and in the activation of several enzymes. The positive influence of increasing the K rate on SS has been shown in several studies with tomato (Liu, Zhang, Tan, & Astatkie, 2011;Sonntag, Naumann, Pawelzik, & Smit, 2019). ** Significant at 1%, * Significant at 5% and Significant at 10%.…”
Section: Resultsmentioning
confidence: 76%